New records of Pennsylvanian phyllocarid crustaceans (Phyllocarida, Archaeostraca) from the Donets Basin, eastern Ukraine - Dernov, Vitaly (Geologos, 2025)
A small phyllocarid faunule comprising Dithyrocaris colei Portlock, 1843, D. cf. granulata Woodward & Etheridge, 1873 and Phyllocarida indet. is described from black shale beds within coal-bearing deposits of the Mospyne Formation (upper Bashkirian, Lower Pennsylvanian) in the central Donets Basin, eastern Ukraine. All records of Carboniferous phyllocarids from the Donets Basin, including those by previous researchers, are preserved in black shales formed under dysaerobic conditions. In the Carboniferous of the Donets Basin, phyllocarids are found predominantly in the Bashkirian interval. Significantly fewer taxa have been recorded from the Serpukhovian, the Serpukhovian/Bashkirian boundary interval and the Upper Pennsylvanian.